Plants are more likely to be spiny at mid‐elevations in the Qinghai‐Tibetan Plateau, south‐western China - Bo Song; Lu Sun; Simcha Lev‐Yadun; Angela T. Moles; Shuang Zhang; Xuelong Jiang; Yongqian Gao; Qi Xu; Hang Sun (Journal of Biogeography, 2020)
Aim We tested the elevational herbivory defence hypothesis, which predicts that plants from low elevations are better defended than plants from higher elevations. Location The Qinghai‐Tibetan Plateau in south‐western China—the world's highest plateau. Taxon Angiosperms. Methods We collated binary spinescence data for 10,622 angiosperm species ranging from 600 to 6,000 m a.s.l. Logistic regression was used to quantify the elevational pattern in spinescence. Because spinescence is thought to be especially effective against mammalian herbivores, we also quantified the association between spinescence and mammalian herbivore richness. Results We found a unimodal relationship between elevation and spinescence, with the highest proportion of spinescent species occurring at mid‐elevations. This unimodal relationship was present in perennial herbs, shrubs and trees, but not in annual herbs. Herbivorous mammal richness also showed a unimodal elevational pattern. A positive association between herbivorous mammal richness and the incidence of spinescent species suggests that elevational variation in herbivore pressure from mammals might drive elevational variation in spinescence. Main Conclusions Our findings further call into question the elevational herbivory defence hypothesis and shed new light on the potential causes of elevational gradients in plant diversity.